(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The article examines the methodology of using innovation and information technology to improve the quality and efficiency of education in "Higher Mathematics". In solving economic problems, practical problems were solved using Mathcad software and the solution was analyzed.